Adaptasi dan Stabilitas Hasil Galur-Galur Padi Beras Merah pada Tiga Lingkungan Tumbuh - Aryana, I Gusti Putu Muliarta (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2009)
The aim of this research was to study the adaptation and yield stability of red rice genotype obtained from back cross selection in three different growing environments. Twenty genotypes of red rice obtained from back cross selection and three parents (Piong, Angka, Kenya) were tested for their potential yield in three different growing environments in the rainy season 2006/2007 and dry season 2007. The experiment used randomized completely block design with three replications in each environment. Each genotype was grown on 5.5 m x 1.25 m plot with plant spacing of 25 cm x 25 cm and only 1 plant per clump. Irrigation in upland was based on the availability of rain water, water management in paddy's field followed a normal lowland rice irrigation technique, and in drought environment, soil water content was maintained at 25 - 30% of soil available water. To analysis the adaptation and the yield stability, analysis of variant AMMI model and Biplot were used. The results indicated that the genotype showing the most stable yield was G5(A4), and this genotype produced 3.60 grain yield ton/ha. Genotype having special adaptation in drought stressed environment were G2(A1) and G3(A2) with average grain yield of 2.93 and 2.11 ton/ha, respectively. Genotype having special adaptation in upland environment were G1(A0) and G4(A3) with average grain yield of 4.43 and 4.44 ton/ha, respectively. Genotype having special adaptation in technical irrigation area was G17(P15) with an average grain yield of 4.92 ton/ha. Key words: Adaptation, stability, red rice